Stigma in relation to families living with parental mental illness: An integrative review. (6th December 2020) - Reupert, Andrea; Gladstone, Brenda; Helena Hine, Rochelle; Yates, Scott; McGaw, Violette; Charles, Grant; Drost, Louisa; Foster, Kim
Abstract: Stigma is a pervasive social mechanism with negative ramifications for people who experience mental illness. Less is known about the stigma experiences of families where a parent has a mental illness. This review aims to identify and synthesize evidence on the concept of stigma and stigma‐related experiences and outcomes reported by parents and children living with parental mental illness. An integrative review method was employed, with PRISMA (Preferred Reporting Items of Systematic Review and Meta‐Analyses) guidelines to search and select literature and extract and analyse data. This approach allows for inclusion of theoretical and empirical literature and for concept definition. Fifty‐eight papers, mostly from the USA, Australia, and the UK, met the inclusion criteria. Stigma was primarily conceptualized in families as a marked difference that was negatively appraised, and which could be internalized. Some articles examined how underpinning assumptions could shape the behaviour of individuals and groups and be embedded within social institutions and structures. For parents, mental illness stigma was interconnected with stigma relating to perceived violations of social and cultural norms related to parenting. Children's experience of stigma resulted in bullying, embarrassment, guilt and social isolation, and efforts to conceal their parent's mental illness. One outcome was that stigma prevented children and parents from seeking much needed supports. Public health policies and campaigns that focus exclusively on promoting open disclosure of mental illness to foster community education outcomes are unlikely to be effective without additional strategies aimed at preventing and redressing the structural impacts of stigma for all family members.